Legal Protection of the Secret Invention. Rights of the Inventor and the Patent Holder - Maneva, Veselina (Yearbook of the Law Department, 2022)
This article analyses the legal regime of the secret invention in the current legislation. The essence of the exclusive right arising from the issued patent and its limitation with a view to the protection of the national security and defence of the country have been investigated. It has been established that the absence of publication of the application and of the issued patent is an obstacle to claiming infringement. The hypotheses of the „free use“ of the patented secret invention are considered. A comparison is made between the rights of the inventor, the patent holder and the user of the invention. Analysed the provisions, relating to the determination of the remuneration of the inventor. Special regard is attributed to the procedure for considering appeals against decisions to terminate proceedings at the Patent Office and to requests for the invalidity of a secret patent, indicating the shortcomings in the current legal framework. A proposal de lege ferenda was formulated to amend the patent law.